Human capital in the national system of labor relations: evaluation criteria, trend analysis, challenges for the future - D.P. Melnychuk (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2015)
The article describes the situation in the sphere of formation and use of human capital. The author formulates direct and indirect criteria that can be used to assess trends and opportunities to use knowledge in the form of capital in Ukraine. The paper carries out the relevant analysis. It argues that the current situation in the sphere of social and labor relations is not conducive to the acquisition of professional knowledge, skills and work skills which are formed as a result of significant investments, the status of capital. This complicates accelerated and anticipated socio-economic development of the state, requires the definition and implementation of decisive steps aimed at streamlining the relations in the sphere of human capital.